Dean Mosman letter to Nicholas S. Halmi regarding bird sightings, June 1, 1978 - Mosman, Deanet al (1978)
Letter from Dean Mosman to Nicholas S. Halmi regarding bird sightings, June 1, 1978. The letter begins by stating that it had been a poor migration year. Notes underlined mention the sightings of a Peregrine Falcon on a kill, a Worm-eating Warbler in Greene County, and Yellow-headed Blackbirds in Ankeny. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed